Preparation and Characterization of Polypyrrole/Montmorillonite Clay Conducting Polymer - Adzmi, Fariz (2007)
In this study, Ppy/MMT nanocomposites have been prepared by polymerization of pyrrole in the presence of FeCl3 as oxidation agent and MMT clay in aqueous medium through the chemical polymerization. The electrical conductivity of the Ppy/MMT nanocomposites was measured by using four-point probe technique. Conductivity of the Ppy/MMT nanocomposites increased from 0.45 to 2.25 S/cm. The increase of conductivity depended on the percentages of Ppy loading in the nanocomposites. Ppy/MMT nanocomposites exhibited similar infra-red (IR) absorption peaks as Ppy and MMT clay. Thereby, confirming the presence of the Ppy and MMT in the products. The X-Ray Diffraction (XRD) patterns revealed, MMT strong peak at 2θ = 6.68º (d-spacing 13.22 Å) and for Ppy/MMT nanocomposites is at 2θ = 4.92º (d-spacing 17.94 Å). The shifting of the angle 2θ is indicated that the insertion of Ppy has occurred. As determined from XRD analyses the crystalline size of MMT is 17.31 Å and is 25.42 Å for Ppy/MMT nanocomposites. Thermal gravimetric analysis (TGA) revealed the improvement of degradation temperature of Ppy is at 157.36 to 177.21 ºC for Ppy/MMT nanocomposites. Scanning electron micrographs (SEM) revealed some interesting morphological differences between the pure MMT clay and Ppy/MMT nanocomposites. The Ppy/MMT nanocomposite exhibits a denser and more compact morphology. Particle formation of irregular and smaller size was clearly revealed by SEM. The effects of several parameters in producing Ppy/MMT nanocomposites were also studied. When percentage of MMT was increased from 1 to 7% the conductivity was decreased from 2.25 to 0.38 S/cm. Result shows higher conductivity for sample prepared at low temperature (~5ºC) compared to room temperature (25ºC). The surface morphology of the Ppy/MMT nanocomposites at low temperature is more compact and denser compared to Ppy/MMT nanocomposites prepared at room temperature. FeCl3 is the suitable oxidation agent to produce Ppy/MMT nanocomposites in aqueous medium. While 6 hours is the suitable preparation time for completion of polymerization of pyrrole.